International University Students’ Experiences Studying Abroad: The Phenomenon of Using English in a Non-English-Speaking Country - Ahmad Nawwal Samhan Abu Aushoth (International Journal of Education, Language, and Religion, 2026)
This qualitative study aims to provide an in-depth understanding of the experiences of international students in Malang, Indonesia. This research examines the gap in the existing literature on BIPA students’ reliance on English as a Lingua Franca during their time studying Bahasa Indonesia. These participants are DARMASISWA awardees who have English proficiency requirements to apply to this program. Meanwhile, locals’ proficiency is demonstrated by low English skills. Interpretative phenomenological analysis was employed to investigate the adaptive strategies and adjustment of three international students to this paradoxical problem. Key findings showed that English plays a role as both a facilitator and a limitation in social contexts beyond the classroom. Participants consistently reported experiencing communication challenges within Indonesian settings, including the use of resulting spontaneous gestures and basic Indonesian language, as well as an evolving reliance on English versus Indonesian dependency, which depended on the time spent in Indonesia. Their unique encounters with both Indonesians and international students shaped their identity in using English and provided new insights into English as a lingua franca in various intercultural contexts. This research revealed the realities of English as a lingua franca in a non-English-speaking country. This highlights the need for research into improving departure guidance and intercultural support for international students.